Establishment of models for plan view pattern control in heavy plate rolling process based on 3-D FEM simulation. (1st January 2013) - Ruan, Jinhua; Zhang, Liwen; Gu, Sendong; Zhang, Jianlin; He, Wenbin; Chen, Shaohui
Basing on a 5 m heavy plate mill, a three-dimensional (3-D) rigid-plastic thermo-mechanical finite element (FE) model was developed to investigate plate plan view pattern (PVP) during hot rolling process. The vertical-horizontal (V-H) rolling was employed to improve plate PVP by preventing width spread. Basing on the FE simulation results of different V-H rolling processes, the plate edging model with short stroke control (SSC) was established with the aid of an artificial neural network (ANN). The compensation rolling was adopted to improve plate PVP by decreasing plate end convexity. The compensation rolling model was established on the basis of the plate PVP prediction model which was formulated by regression analysis of the simulation results of conventional rolling processes with different broadside rolling ratios. Simulation results showed that optimal combination of V-H rolling and compensation rolling can improve the plate PVP to a large extent.